The delocalisation of mafia organisations and the construction of a European law against organised crime. Issue 1 (2nd January 2016) - Balsamo, Antonio
Abstract : This article suggests how to interpret the changing reality of the Italian mafia associations, which are tending to add a transnational economic dimension to their original territorial-ethnic matrix, and describes the cultural backgrounds behind the different approaches of Italian courts to the delocalisation of criminal groups. After highlighting the evolution of the Italian system of patrimonial prevention measures against organised crime from a comparative viewpoint, the article reviews the positive and negative features of the new Anti-Mafia Code and of the European directive on confiscation of instrumentalities and proceeds of crime, indicating finally some guidelines for a future European anti-mafia legislation.